Did You Just Lie to Me? Deception Detection in Face to Face versus Computer Mediated Communication. Issue 5 (3rd September 2022) - Eskritt, Michelle; Fraser, Brandon; Bosacki, Sandra
ABSTRACT: Individuals' deception detection ability during either a face-to-face (FtF) interaction or through computer-mediated communication (CMC) was explored under more naturalistic conditions where they were not forewarned that deception may be involved. Participants discussed a social issue either in a room together or by instant messaging from separate rooms. Prior to discussion, some participants were asked to deceive their partner regarding their actual opinion on the issue. Results showed that mode of communication did not influence participants' deception detection accuracy rate, nor their truth bias. Regardless of mode of communication, deceptive participants experienced the same level of physiological arousal as the non-deceivers. In contrast, deceivers reported experiencing higher levels of anxiety but only in the FtF condition. Findings highlight how for different communication modalities, a multitude of interactive factors may influence deception detection.